Integrated post-occupancy evaluation and intervention that achieve real-world zero-carbon buildings - Lizana, J; Wheeler, S; Azizi, E; Halloran, C; Wheeler, J; Wallom, DCH; McCulloch, M (Elsevier, 2023)
Many building standards are available worldwide to support sustainable building design. However, most of them only define compliance before occupancy, overlooking the real building usage and its implications for meeting zero-carbon targets. This research proposes a systematic post-occupancy evaluation and intervention (POEI) protocol to analyse real building performance and support cost-effective and zero-carbon upgrading. The novelty lies in integrating novel diagnostic data science techniques to identify performance gaps, advanced physics-driven energy modelling iteratively calibrated with POE data to disaggregate energy use by end-use, and cost-optimal intervention analysis. The POEI protocol has been validated in a university building. The results demonstrated the POEI benefits for the cost-optimal upgrading of in-use building assets based on real needs. By optimising control, reducing demand, increasing efficiency, and implementing renewables, the building can reach the nearly zero-carbon building target with a payback period of 13 years and a 23 % lower life-cycle cost compared to the baseline scenario. Building energy management interventions were identified as the most important actions to reduce the performance gap, reducing energy consumption by 20 % and carbon emissions by 24 %. The results also highlight the critical role of Information and Communication Technologies (ICT), which may represent up to 49 % of energy use in the future zero-carbon building scenario if overlooked.